Analisis Laporan Arus Kas PT. HM Sampoerna - Popi Sopiah; Siti Halimah; Ayunda Fitra Utami; Nur Hidayah K Fadhilah (Ekonomia, 2021)
The statements of cash flows is a financial statement cash receipts, cash payments, and net cash changes from operating, investing and financing activities over a period.The purpose of the research is 1 to analyze the cash flow statements of PT. Hanjaya Mandala Sampoerna Tbk, 2. To find a picture of the cash flow statement on Handjaya PT Mandala Sampoerna Tbk Listed in Indonesia Stock Exchange. 3. To determine the financial performance Handjaya Mandala Sampoerna Tbk Listed in Indonesia Stock Exchange. Data analysis techniques used in this research is a qualitative descriptive analysis, comparative analysis, and inductive analysis. The results of this study can be concluded the ratio of cash flow shows the financial situation is not good, because of the overall ratio is likely to decline and has a value below 1. Only 2 ratio rated good that the flow of funds and the coverage ratio of cash flow adequacy ratio.